2018
DOI: 10.1097/cji.0000000000000206
|View full text |Cite
|
Sign up to set email alerts
|

Eomesodermin Increases Survival and IL-2 Responsiveness of Tumor-specific CD8+ T Cells in an Adoptive Transfer Model of Cancer Immunotherapy

Abstract: Tumor-specific CD8 T cells often fail to elicit effective antitumor immune responses due to an inability to expand into a substantial effector population and persist long-term in vivo. Using an adoptive transfer model of cancer immunotherapy, we demonstrate that constitutive eomesodermin (Eomes) expression in tumor-specific CD8 T cells improves tumor rejection and survival. The increase in tumor rejection was associated with an increased number and persistence of CD8 T cells in lymphoid tissues during acute tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
2
3
0
Order By: Relevance
“…However, in the CLL mouse model, we observed no major impact of EOMES on the differentiation or functional capacity of CD8 + T cells, which might be due to the overlapping function of EOMES with the phylogenetically related transcription factor T-BET [ 5 , 8 ]. Our data, however, show that EOMES is required for efficient CD8 + T-cell expansion, which is in line with a previously described role of EOMES in enhancing CD8 + T-cell proliferation and survival and thereby, improving tumor control in a mouse model of cancer immunotherapy [ 42 ]. The importance of EOMES in adaptive immune control of tumors is further exemplified by a subset of CD4 + T cells that expresses EOMES and shows cytotoxic activity [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, in the CLL mouse model, we observed no major impact of EOMES on the differentiation or functional capacity of CD8 + T cells, which might be due to the overlapping function of EOMES with the phylogenetically related transcription factor T-BET [ 5 , 8 ]. Our data, however, show that EOMES is required for efficient CD8 + T-cell expansion, which is in line with a previously described role of EOMES in enhancing CD8 + T-cell proliferation and survival and thereby, improving tumor control in a mouse model of cancer immunotherapy [ 42 ]. The importance of EOMES in adaptive immune control of tumors is further exemplified by a subset of CD4 + T cells that expresses EOMES and shows cytotoxic activity [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, a recent report showed that constitutive expression of Eomes in tumor-specific CD8 T cells improved tumor rejection in a mouse lymphoma model system (EG7; ref. 32). These findings support a positive immune regulatory role of Eomes in cancer, which is in contrast to our observation that Eomes suppresses CD8 T-cell response in AML patients.…”
Section: Discussionsupporting
confidence: 70%
“…In this line, the coexpression of STAT4 and EOMES was indeed reported in effector T-cells. 64 Some molecules involved in T-cell cytotoxicity against tumor cells were upregulated (PRF1, GZM …).…”
Section: Discussionmentioning
confidence: 99%